Functional Thyroid Follicular Cells Differentiation from Human-Induced Pluripotent Stem Cells in Suspension Culture - Arauchi, Ayumi; Matsuura, Katsuhisa; Shimizu, Tatsuya; Okano, Teruo (Frontiers in Endocrinology, 2017)
The replacement of regenerated thyroid follicular cells (TFCs) is a promising therapeutic strategy for patients with hypothyroidism. Here, we have succeeded in inducing functional TFCs from human induced pluripotent stem cells (iPSCs) in scalable suspension culture. Differentiation of iPSCs with Activin A treatment produced Sox17- and FoxA2-expressing definitive endodermal cells that also expressed thyroid transcription factors Pax8 and Nkx2-1. Further treatment with thyroid-stimulating hormone (TSH) induced TFCs expressing various types of thyroid proteins including TSH receptor, sodium-iodide symporter, thyroglobulin and thyroid peroxidase. Interestingly, differentiated cells secreted free thyroxine in vitro. These results indicate successful differentiation of human iPSCs to functional TFCs that may enable us to fabricate thyroid tissues for regenerative medicine and disease models.